PERTANGGUNG JAWABAN PIDANA PEJABAT ADMINISTRASI NEGARA YANG TIDAK MEMPEROLEH KEUNTUNGAN DALAM TERJADINYA TINDAK PIDANA KORUPSI (Studi Kasus No.12/Pid.sus-TPK/2018/PN.PGP) - Arief Budiman; Evi Deliana; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The rampant criminal acts of corruption in Indonesia are not only detrimental to Statefinances, but have been a violation of the social and economic rights of the community at large. corruptionis no longer a national problem, but has become a transnational phenomenon so that internationalcooperation becomes essential in preventing and eradicating it. unusual efforts are needed, butextraordinary efforts in the handling and eradication of criminal acts of corruption. One of the efforts thatcan avoid the deterioration of Indonesia due to corruption is to make efforts to seize and return to assetsresulting from criminal acts of corruption that are based on legislation in force in the Indonesian positivelegal system. However, many state administration officials were caught in corruption cases because theymisused the authorities that were in them. The limits of this authority should be more clearly formulated, sothat what kind of authority can be said to violate the authority in Administrative Law, and violation ofauthority as what is said to be a violation of the Corruption Crime authority. Based on this exaggeration,the author identifies two formulations of the problem, First What is the criminal responsibility of stateAdministration officials who do not benefit from the occurrence of criminal acts of corruption. Second, howis the judge's judgment in deciding the case of corruption.This type of research can be classified in normative juridical research, because this research isconducted by examining secondary data and approaches to law, this normative research examines theprinciples of legal principles of law. The data sources used are, primary data, secondary data, tertiary data,data collection techniques in this study are normative juridical, the data used is library research.Based on the results of the research and the problems in this study is the criminal responsibility forcases of corruption in the distribution of rotating funds LPDB-KUMKM which was decided by the panel ofjudges against the defendant in favor of the maharta in accordance with Article 3 of Law no. 31 of 1999concerning Corruption Crime jo Law no. 20 of 2001 concerning Amendments to Law Number 31 of 1999concerning Eradication of Corruption Crime, namely the existence of an element of abuse of authority fromthe perpetrators, in addition to the absence of forgiving reasons as justification. As for the judges'consideration in imposing criminal sanctions on perpetrators due to legal factors, the loss of state finances,to which the defendant committed corruption and the elements contained in the indictment of the publicprosecutor.Keywords: Corruption, Criminal Accountability